Experimental and theoretical studies of Znq₂ thin film fabricated by spin-coating and its characterisation as an active layer in OLED - Sypniewska, Małgorzata; Brumboiu, Iulia E.; Kaczmarek-Kedziera, Anna; Pokladko-Kowar, Monika; Gondek, Ewa; Popielarski, Paweł; Szczęsny, Robert; Derkowska-Zielinska, Beata (Opto-Electronics Review, 2025)
Bis(8-hydroxyquinoline) zinc dispersed in a poly(N-vinylcarbazole) matrix (Znq2:PVK) was characterised for its possible use as an active layer in organic light-emitting diodes. The composition and morphology of Znq2:PVK thin films deposited on quartz substrates was analysed by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and confocal microscopy. Optical properties of the films were characterised by absorption spectroscopy and photoluminescence and explained on the basis of calculated molecular properties of gas phase Znq2, N-vinylcarbazole pentamer, and molecular models for the Znq2:PVK interface. FTIR measurements of the Znq2:PVK film revealed the presence of water, likely due to the formation of Znq2-dihydrate during the fabrication process. Water could be removed by annealing films at 130 °C for 1 h and the annealed films showed better photoluminescence in the Znq2 emission region. Finally, two diodes with an ITO/PEDOT:PSS/Znq2:PVK/Al structure were fabricated, where in the second one, the ITO/PEDOT:PSS/Znq2:PVK layers were annealed at 130 °C. The first diode was characterised by a maximum brightness of about 83 cd/m2 and a current efficiency of 0.12 cd/A, while the diode whose structure was annealed had a maximum brightness of about 219 cd/m2 and a current efficiency of 0.26 cd/A.